2001
DOI: 10.1017/s003382220003798x
|View full text |Cite
|
Sign up to set email alerts
|

Is Classical Acid-Alkali-Acid Treatment Responsible for Contamination? An Alternative Proposition

Abstract: It is well known that, during the widely used AAA pretreatment (de Vries and Barendsen 1954), alkali treatment is responsible for the incorporation of modern carbon due to the precipitation of atmospheric CO2 as carbonate. Until now, the last step of the experiment, consisting in acid treatment (most of the time with hydrochloric acid) was considered to be sufficient to eliminate all of lab contamination. But wood, peat and sediment present a complex molecular structure. During radiocarbon chemical treatments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 10 publications
0
60
1
Order By: Relevance
“…To address the issue of a detailed chronology for the Last Glacial, the dating of loess bulk organic matter has been used throughout the Nussloch loess sequence (50). Despite a better precision than for OSL ages, these results show age underestimations and inversions, especially for tundra gley horizons (51). In addition, radiocarbon ages are, like feldspar OSL ages (14,52,53), significantly younger than quartz OSL and thermoluminescence ages (54)(55)(56).…”
Section: Methodsmentioning
confidence: 77%
“…To address the issue of a detailed chronology for the Last Glacial, the dating of loess bulk organic matter has been used throughout the Nussloch loess sequence (50). Despite a better precision than for OSL ages, these results show age underestimations and inversions, especially for tundra gley horizons (51). In addition, radiocarbon ages are, like feldspar OSL ages (14,52,53), significantly younger than quartz OSL and thermoluminescence ages (54)(55)(56).…”
Section: Methodsmentioning
confidence: 77%
“…The ABA (or AAA for acid-alkali-acid) method is commonly used in laboratories. However, several studies (Hatte`et al, 2001 and references given therein) have shown that in some materials the alkali step of ABA might be responsible for contamination with modern carbon from atmospheric CO 2 dissolved in the base and incorporated into the sample structure. Such contamination cannot be entirely removed by the last acid step if the commonly used HCl solution is applied.…”
Section: Radiocarbon Dating Of Wood and Peatmentioning
confidence: 99%
“…The modified preparation techniques of Hatte`et al, (2001) and the ABOX technique of Bird et al, (1999), respectively, were applied to clean peat and wood samples. This involved a replacement of the last step (weak HCl) of the ABA protocol treatment with weak HCl with a H 2 SO 4 treatment.…”
Section: Background Correction and Sample Preparationmentioning
confidence: 99%
“…The CO 2 gas was prepared using three different protocols chosen according to the type of sediment. The protocol from Hatté et al (2001c) (HCl 0.6 N, Na 4 P 2 O 7 0.1 M and HCl 1 N at room temperature) was applied for typical loess sediment, whereas either protocol from Hatté et al (2001b) (HCl 0.6 N, Na 4 P 2 O 7 0.1 M, K 2 Cr 4 O 7 0.1 M/H 2 SO 4 2 N at room temperature) was applied to sediment extracted from gleys under N 2 flow to avoid possible incorporation of modern CO 2 during alkali treatment by adsorption on Fe 2+ . All 14 C measurements were converted to calendar ages using Calib 6.0, which includes the IntCal09 calibration (Reimer et al, 2009).…”
Section: C Datingmentioning
confidence: 99%